Secure Key Exchange Using Boolean algebra: A New Method Based on NP-Hard Problem - Ahmed, Khamiss; Albrkoli, Mohammed; Alfitouri, Aisha; Alawan, Mahmmoud (Scientific Journal for Faculty of Science-Sirte University, 2023)
Secure key exchange is essential for maintaining the confidentiality and integrity of transmitted data in contemporary communication systems. To restrict unwanted access to the transferred keys, traditional key exchange techniques relied on computational complexity. Traditional approaches could be attacked, though, if modern computing resources become more powerful. This article suggests a novel method for secure key exchange based on NP-hardness and Boolean algebra. The method creates a public value from the private keys of two participants and other information, and each person then uses their own private key and the other public value to obtain the shared key. The fact that the private keys are not disclosed and that both users compute the secret key using their respective sets of private keys and values received from the other side makes the system resistant to man-in-the-middle attacks. The major goal of the suggested solution is to safely retrieve the same value as a shared key for both participants, even if others already know the public values. Boolean algebra and an NP-hard issue offer higher security assurances than conventional techniques that only consider computational complexity. The study uses a key size of 128 bits, which produces good results and offers higher security guarantees than conventional techniques. The study has also created a brand-new key exchange strategy that enhances current methods. Overall, this method marks a substantial advancement in the use of Boolean algebra and NP-hard issues to achieve secure key exchange.